O fenômeno da indisciplina na escola :O sistema preventivo de Dom Bosco como estratégia para controlar a indisciplina nos jovens de 15 a 17 años da Escola Estadual Professora Wanda Bento Goçalves no ano de 2009 - Ferreira García, Everaldo (2010)
The present dissertation it is constituted in study on the phenomenon of the no discipline in the school institutions. The central objective went watch ruptures and present contradictions in the speech of the common sense that attributes to the student the great portion of responsibility in what he/she says respect to the subjects you discipline, showing that Dom Bosco's preventive method comes as a viable alternative and checked for the solution of the problems of acts the no discipline in the school atmosphere. The revision of the pertinent literature to the thematic was used for the construction of the text that is prayed it presents, tends for bases the studies of Aquino, 1996; 1998; 1999; Braido, 2004; Bosco, 2004; Vasconcellos, 1994, among others. The challenge that is placed the educator of the century XXI is the challenged to redirect their actions in order to better contribute with the construction of an effective education for the citizenship, one that instrument the youths to became critical and productive actors of a less exclusivist society, where they can feel included.